Mesoproterozoic seafloor authigenic glauconite-berthierine: indicator of enhanced reverse weathering on early Earth; American Mineralogist; Vol. 107, iss. 1 - Ma Jianbai; Shi Xiaoying; Lechte Maxwell; Zhou Xiqiang; Wang Zhenfei; Huang Kangjun; Tang Dongjie; Rudmin M. A. Maksim Andreevich (2022, 2022)
Title screen